Vibrio parahaemolyticus isolated from live shellfish marketed in Korea: antibiotic and heavy metal resistance - Masimbule Vidanalage Kasun Sameera Wickramanayake; Sana Majeed; Prasanga Madhushani Kumarage; Gang-Joon Heo (Veterinary Integrative Sciences)
This study examined the antibiotic and heavy metal resistance properties in Vibrio parahaemolyticus isolated from Korea's five most popular shellfish. Thirty-four V. parahaemolyticus isolates were isolated by conducting biochemical tests and PCR. Isolation frequencies were 4 (cockles), 2 (scallops), 2 (mussels), 1 (Pacific abalone), and 25 (white-leg shrimp). The disc diffusion method was employed to detect antibiotic resistance. All isolates were resistant to ampicillin. Piperacillin, colistin, and vancomycin resistance were detected in 82%, 68%, and 50% of the isolates, respectively. Thirty-two isolates were multidrug resistant [Multiple Antibiotic Resistance (MAR) index ≥0.2]. β-lactam resistant blaSHV gene was the most prevalent gene detected in 68% of the isolates in PCR assays. In addition, blaCTX, aac(6’)-Ib, and blsTEM were detected in 21%, 44%, and 6% of the isolates, respectively. Phenotypic resistance to Pb, Cd, and Cu was detected in 25, 4, and 3 isolates, respectively in broth dilution test. CzcA gene was the prevalent detected in 16 isolates, followed by CopA and merA genes detected in 11 and 7 isolates, respectively. The findings of this study suggest that live shellfish marketed in Korea are a potential source of antibiotic-resistant V. parahaemolyticus.